2001
DOI: 10.1002/1097-0215(200002)9999:9999<::aid-ijc1022>3.3.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Glycoprotein 90K/MAC‐2BP interacts with galectin‐1 and mediates galectin‐1–induced cell aggregation

Abstract: The glycoprotein 90K was originally described as a tumor‐secreted antigen and subsequently found to have immunostimulatory activity as well as other possible functions. This protein interacts with an endogenous lectin, galectin‐3, and may play a role in tumor metastasis through this interaction. Because 90K is heavily glycosylated, it may also interact with other members of the galectin family, which would contribute to the multifunctionality of 90K. To test this possibility, we studied the recognition of 90K … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(49 citation statements)
references
References 39 publications
1
46
0
2
Order By: Relevance
“…15,16 It was also found that M2BP serves as a ligand for galectin-1 and mediates the cell-aggregating activity by this lectin. 27 These characteristics allow us to assume that M2BP is responsible for metastatic activity of cancer cells. 28 On the other hand, M2BP is thought to play a part in cellular immune responses in hosts.…”
Section: Anti-m2bp Antibody In Sera From Patients With Lung Carcinomamentioning
confidence: 99%
“…15,16 It was also found that M2BP serves as a ligand for galectin-1 and mediates the cell-aggregating activity by this lectin. 27 These characteristics allow us to assume that M2BP is responsible for metastatic activity of cancer cells. 28 On the other hand, M2BP is thought to play a part in cellular immune responses in hosts.…”
Section: Anti-m2bp Antibody In Sera From Patients With Lung Carcinomamentioning
confidence: 99%
“…Moreover, several reports have shown that the protein may function in cell adhesion processes. In particular, it has been demonstrated that Mac-2BP, as a ligand of galectin-1, -3, and -7, may promote homotypic cell-to-cell contacts (11,12), or may regulate cell adhesion by binding to cellular matrix proteins including β1-integrin, collagens, and fibronectins (13). Therefore, Mac-2BP may favor the establishment of new tumor colonies via enhancement of adhesive interactions between tumor cells and the extracellular matrix (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…For example osteopontin from human bone shows only two N-glycans with binding sites which are partially blocked by 6-bound sialic acid (Ideo et al, 2003;Masuda et al, 2000;Stowell et al, 2008a). Another extracellular matrix protein interacting with galectin-1 and -3 is the Mac-2 binding protein or 90K antigen which influences adhesion processes (Sasaki et al, 1998;Tinari et al, 2001). The different ECM-proteins which are bound by galectins can interact with other ECMglycoproteins and/or integrins (Adams, 2001;Janik et al, 2010;Kariya et al, 2008;Singh et al, 2010).…”
Section: Ecm Glycoproteins As Binding Partners Of Galectinsmentioning
confidence: 99%